Asymptotic behaviour for a phase field model in higher order sobolev spaces - Jimenez-casas, A.; Rodriguez-bernal, A. (Revista Matemática Complutense, 2002)
In this paper we analyze the long time behavior of a phase– field model by showing the existence of global compact attractors in the strong norm of high order Sobolev spaces.